SCAFOLDING DALAM MENYELESAIKAN SOAL EKSPONEN MAHASISWA DITINJAU DARI TEORI BRODIE - Fhela Vhantoria (Universitas Muhammadiyah Kotabumi, 2021)
The purpose of describing scaffolding in solving student exponential problems in terms of Brodie's theory. Qualitative descriptive method. Data were collected using tests and interviews with first-semester students of the Mathematics Study Program, University of Muhammadiyah Kotabumi. Research subjects 4 of 28 students of mathematics education study program. In classifying the types of errors using Brodie's theory, namely 1) basic error, 2) appropriate error, 3) missing information, and 4) partial insight. Then the way to overcome student errors is given by scaffolding based on Anghileri's theory, namely environmental provisions, (explaining, reviewing, and restructuring), and developing conceptual thinking. The results of study 1) students' errors in solving exponential questions on basic errors, namely misunderstanding the questions, 2) meaningful learning helps students to better understand the questions, 3) scaffolding is carried out based on the three levels of Anghileri scaffolding, and 4) scaffolding is given in the form of directives so that students better understand the problem.